Opuntia ficus-indica cladodes as a functional ingredient: bioactive compounds profile and their effect on antioxidant quality of bread. Issue 1 (December 2017) - Msaddak, Lotfi; Abdelhedi, Ola; Kridene, Amani; Rateb, Mostafa; Belbahri, Lassaâd; Ammar, Emna; Nasri, Moncef; Zouari, Nacim
Abstract Background In the context of a balanced diet, the antioxidant-rich food consumption is a preventive way of many degenerative diseases. Consequently, improving the nutraceutical quality of traditional foods such as bakery products is an interesting approach. Considering the present consumer's demand, cladodes from prickly pear that were traditionally used as a valuable food as well as in folk medicine for the treatment of several chronic diseases were investigated for their use in bread production to improve its functionality. Methods Bioactive substances were determined by liquid chromatography-high resolution electrospray ionization mass spectrometry (LC-HRESIMS) analysis. Dough rheological properties were characterized by alveographic measurements. Bread antioxidant quality was evaluated by total phenolics content, DPPH radical-scavenging, metal (Fe2+ ) chelating and Fe3+ reducing power determinations. Results LC-HRESIMS analysis of the cladodes extract allowed the identification of 9 flavonoids, 2 phenolics, 1 alkaloid and 1 terpenoid compounds. Cladodes powder enrichment induced important modifications on the dough rheological parameters in terms of the extensibility (L) and deformation energy (W) decrease. Moreover, cladodes powder addition to bread resulted in a decrease in both crust and crumb colour parameters (L *, a * andb *). A 5% supplementation resulted in an increase of the bread yield and bread specific volume by 8.9 and 25%, respectively. Interestingly, Bread containing cladodes powder showed enhanced total phenolics content and antioxidant potential as compared to the control. Conclusions Substitution of wheat flour by the cladodes powder at 5% level was optimal for improving the total phenolics content and the antioxidant potential of bread without having any negative effect on its sensory acceptability. Cladodes fromOpuntia ficus -indica could be considered as a potential health-promoting functional ingredient in bakery products.